Furoic acid and derivatives as atypical dienes in Diels-Alder reactions - Cioc, Răzvan C; Smak, Tom J; Crockatt, Marc; van der Waal, Jan C; Bruijnincx, Pieter C A (Green chemistry : an international journal and green chemistry resource : GC, 2021)
The furan Diels-Alder (DA) cycloaddition reaction has become an important tool in green chemistry, being central to the sustainable synthesis of many chemical building blocks. The restriction to electron-rich furans is a significant limitation of the scope of suitable dienes, in particular hampering the use of the furans most readily obtained from biomass, furfurals and their oxidized variants, furoic acids. Herein, it is shown that despite their electron-withdrawing substituents, 2-furoic acids and derivatives (esters, amides) are in fact reactive dienes in Diels-Alder couplings with maleimide dienophiles. The reactions benefit from a substantial rate-enhancement when water is used as solvent, and from activation of the 2-furoic acids by conversion to the corresponding carboxylate salts. This approach enables Diels-Alder reactions to be performed under very mild conditions, even with highly unreactive dienes such as 2,5-furandicarboxylic acid. The obtained DA adducts of furoic acids are shown to be versatile synthons in the conversion to various saturated and aromatic carbocyclic products.